2022
DOI: 10.1111/acer.14763
|View full text |Cite
|
Sign up to set email alerts
|

Reduced calibration between subjective and objective measures of episodic future thinking in alcohol use disorder

Abstract: Background A reduced capacity to mentally simulate future scenarios could be of clinical importance in alcohol use disorder (AUD). However, little is known about the mechanisms underlying episodic future thinking (EFT) impairment in AUD. Methods We tested patients with severe AUD using two measures of EFT: the individual's own subjective experience of their imaginings (phenomenology) and the objective number of details included in imagined events, as assessed by an independent observer (examination). The compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…It is worth noting that there was no association between self-rated goal quality and experimenter-coded goal specificity. This finding is consistent with a recent experiment in which no correlation was found between self- and experimenter-ratings of future events in individuals with alcohol use disorder, in contrast to healthy controls in which these measures did correlate (Noël et al, 2022 ). One possible explanation is that individuals with more severe symptoms lack insight into the reduced quality of their goals, so self- and experimenter-rated indices of goal quality diverge as level of severity increases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is worth noting that there was no association between self-rated goal quality and experimenter-coded goal specificity. This finding is consistent with a recent experiment in which no correlation was found between self- and experimenter-ratings of future events in individuals with alcohol use disorder, in contrast to healthy controls in which these measures did correlate (Noël et al, 2022 ). One possible explanation is that individuals with more severe symptoms lack insight into the reduced quality of their goals, so self- and experimenter-rated indices of goal quality diverge as level of severity increases.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to healthy controls, individuals with alcohol use disorder showed reduced specificity for both the past and future events, suggesting a more general reduction in specificity of episodic thinking. Another three studies have shown that individuals with alcohol use disorder generated less detailed descriptions of future events compared to healthy controls (Mercuri et al, 2016 ; Nandrino & El Haj, 2019 ; Noël et al, 2022 ), although one study has reported a null difference (Moustafa et al, 2018 ). Finally, Mercuri et al ( 2018 ) observed reduced specificity of future event descriptions in regular but not recreational cannabis users compared to controls, suggesting that this characteristic may increase with dependence severity.…”
Section: Introductionmentioning
confidence: 99%
“…52 Therefore, there are differences in the degree of cognitive impairment caused by aldehyde accumulation during chemotherapy. 53,54 Recent studies have confirmed that ALDH2 in astrocytes is involved in the regulation of behavioural and cognitive functions related to ethanol metabolism in the brain. 55 Both chemotherapy-and ethanol metabolisminduced cognitive impairment can be caused by aldehydes 42,56 ; thus, ALDH2 in the brain may also affect CRCI by participating in aldehyde regulation.…”
Section: Discussionmentioning
confidence: 96%
“… 52 Therefore, there are differences in the degree of cognitive impairment caused by aldehyde accumulation during chemotherapy. 53 , 54 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation